2005
DOI: 10.1016/j.femsec.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial immobilization and remineralization of N at different growth rates and N concentrations

Abstract: An experiment was designed to resolve two largely unaddressed questions about the turnover of N in soils. One is the influence of microbial growth rate on mobilization and remineralization of cellular N. The other is to what extent heterotrophic immobilization of NO(3)(-) is controlled by the soil concentration of NH(4)(+). Bacteria were extracted from a deciduous forest soil and inoculated into an aqueous medium. Various N pool dilution/enrichment experiments were carried out to: (1) calculate the gross N imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…However, caution is needed when interpreting these results: plant communities dominated by fast‐growing, resource‐exploitative species and their associated microbial communities might rapidly take up available N, but high rates of nutrient cycling also mean that N is remineralized (Bengtson & Bengtsson, 2005) and potentially lost quickly from ecosystems. We did not measure this process, but it can be relevant at longer timescales.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is needed when interpreting these results: plant communities dominated by fast‐growing, resource‐exploitative species and their associated microbial communities might rapidly take up available N, but high rates of nutrient cycling also mean that N is remineralized (Bengtson & Bengtsson, 2005) and potentially lost quickly from ecosystems. We did not measure this process, but it can be relevant at longer timescales.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained that this observation was maybe due to nitrate immobilization by root or by microorganisms, rather than nitrification activities. Nitrifying microorganisms could be inhibited by heterotrophic bacteria in N-poor environments such as the glacier foreland (Bengtson and Bengtsson 2005), while nitrogen fixation and ammonification could guarantee the ammonium amount in these soils.…”
Section: Microbial Role In Nutrient Cycling In High Mountain Environmmentioning
confidence: 99%
“…In fact, Verhagen et al [83] and Bengtson and Bengtsson [8] reported that nitrifying bacteria are outcompeted by heterotrophic bacteria in ammoniumpoor environments. In contrast, microbial nitrogen fixation and ammonification may explain the sustainability of the ammonium pool.…”
Section: Nitrogenase Activity and Soil Biogeochemistrymentioning
confidence: 99%